The resident experience with psychological safety during interprofessional critical event debriefings. Issue 2 (1st April 2023) - Hitchner, Lily; Yore, Mackensie; Burk, Charney; Mason, Jessica; Sawtelle Vohra, Stacy
Abstract: Objectives: Interprofessional feedback and teamwork skills training are important in graduate medical education. Critical event debriefing is a unique interprofessional team training opportunity in the emergency department. While potentially educational, these varied, high‐stakes events can threaten psychological safety for learners. This is a qualitative study of emergency medicine resident physicians' experience of interprofessional feedback during critical event debriefing to characterize factors that impact their psychological safety. Methods: The authors conduced semistructured interviews with resident physicians who were the physician team leader during a critical event debriefing. Interviews were coded and themes were generated using a general inductive approach and concepts from social ecological theory. Results: Eight residents were interviewed. The findings suggest that cultivating a safe learning environment for residents during debriefings involves the following: (1) allowing space for validating statements, (2) supporting strong interprofessional relationships, (3) providing structured opportunities for interprofessional learning, (4) encouraging attendings to model vulnerability, (5) standardizing the process of debriefing, (6) rejecting unprofessional behavior, and (7) creating the time and space for the process in the workplace. Conclusions: Given the numerous intrapersonal, interpersonal, and institutional factors at play, educators should be sensitive to times when a resident cannot engage due to unaddressed threats to their psychological safety. Educators can address these threats in real time and over the course of a resident's training to enhance psychological safety and the potential educational impact of critical event debriefing.